2003
DOI: 10.1152/ajpheart.01112.2002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in hypothermia linked to redistribution of oxygen in brain

Abstract: Hypothermia improves the outcome of acute ischemic stroke, traumatic injury, and inflammation of brain tissue. We tested the hypothesis that hypothermia reduces the energy metabolism of brain tissue to a level that is commensurate with the prevailing blood flow and hence allows adequate distribution of oxygen to the entire tissue. To determine the effect of 32 degrees C hypothermia on brain tissue, we measured the sequential changes of physiological variables by means of PET in pigs. Cerebral blood flow and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 63 publications
3
50
0
3
Order By: Relevance
“…3,4 The physiological benefits of TH are thought to be multifactorial, including decreases in cerebral oxygen demand and direct cellular effects and a reduction in reactive oxygen species generation. 42 Despite the recommendation that hypothermia should be initiated as soon as possible after cardiac arrest, the method, timing, and duration of hypothermia treatment have yet to be comprehensively studied. Hypothermia can be induced by a variety of different methods, including surface cooling, ice-cold infusions, evaporative transnasal cooling, and endovascular cooling catheters.…”
Section: Circulatory Supportmentioning
confidence: 99%
“…3,4 The physiological benefits of TH are thought to be multifactorial, including decreases in cerebral oxygen demand and direct cellular effects and a reduction in reactive oxygen species generation. 42 Despite the recommendation that hypothermia should be initiated as soon as possible after cardiac arrest, the method, timing, and duration of hypothermia treatment have yet to be comprehensively studied. Hypothermia can be induced by a variety of different methods, including surface cooling, ice-cold infusions, evaporative transnasal cooling, and endovascular cooling catheters.…”
Section: Circulatory Supportmentioning
confidence: 99%
“…In newborn pigs (papers II and III), therapeutic hypothermia reduced histopathological damage, although statistically significant only in pigs reoxygenated with 100% oxygen and not after reoxygenation with air. It has been suggested that hypothermic neuroprotection is linked to redistribution of oxygen in the brain, as moderate hypothermia in some models reduces cerebral blood flow, decreases metabolic rate and reduces neuronal oxygen uptake 173,[292][293][294] . We did not observe any decrease in striatal microcirculation in the pig model, but found increased striatal oxygen tension in hypothermic compared to normothermic animals.…”
Section: Therapeutic Hypothermiamentioning
confidence: 99%
“…To determine whether changes in CBF during HI were linked to cellular metabolism [12,19] independent of NO, we performed HI under conditions of mild hypothermia (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%